Cohort profile: the Lanxi Cohort study on obesity and obesity-related non-communicable diseases in China. Issue 5 (9th May 2019) - Wei, Chen; Ye, Sunyue; Ru, Yuan; Gan, Da; Zheng, Weifang; Huang, Chao; Chen, Lijin; Gao, Peng; Li, Jiayu; Yang, Min; Yang, Fei; Zhao, Xueyin; et al.
Abstract : Purpose: The Lanxi Cohort was established to systematically investigate the aetiology and interplay of body fat distribution and multiple factors with obesity and obesity-related non-communicable diseases in China. Participants: The baseline investigation of the Lanxi Cohort study took place between June 2015 and August 2017 in Lanxi, Zhejiang Province, China. Permanent residents from one urban community and four rural villages were involved in this study. The baseline investigation included questionnaire survey, physical examination, dual-energy X-ray absorptiometry (DXA) scan, blood samples collection and traditional Chinese medicine (TCM) inquiry. Findings to data: A total of 5132 participants, aged 18 to 80 years, were recruited at baseline; among them, 38.7% were men and 64.8% were from the urban area. The mean age was 53.04±12.77 years. The completion rates of physical examination, DXA scan, blood collection and TCM inquiry were 99.9%, 98.5%, 99.9% and 96.5%, respectively. The mean body mass index (BMI) was 23.42±3.20 kg/m 2 with 8.1% of the study population being obese (BMI ≥28 kg/m 2 ). The crude prevalence of hypertension, diabetes and metabolic syndrome were 34.9%, 10.0% and 30.4%, respectively. Future plans: All participants will be monitored annually for cause-specific mortality and morbidity and hospital admission and will be followed up by in-person survey every 4 years. The baseline population is considered to expand in the future depending on the availability of funding support. Ethics approval: This study was approved by the Ethical Committee of the School of Public Health, Zhejiang University.